Cultural Context Representation in the Merdeka Curriculum English Textbook: A Content Analysis - Nabilah Ningrum; Wisma Yunita (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study explores the representation of cultural contexts in the English for Change textbook, a key resource for senior high school students under Indonesia’s Merdeka Curriculum. The research investigates how target, source, and international cultures are portrayed, assessing their role in fostering intercultural communication skills. Using qualitative content analysis, supported by quantitative insights, the study applies frameworks to evaluate cultural content. The textbook achieves a numerical balance on target culture (32%), source culture (36%), and international culture (32%). However, it lacks depth in cultural exploration. Target culture often centers on basic practices, source culture is fragmented, and international culture tends to focus on global challenges rather than meaningful intercultural exchanges. Themes such as environmental awareness, digital literacy, and financial management dominate, but opportunities for critical cultural dialogue are largely missed. These findings reveal that the textbook while promising, falls short of fully supporting students’ intercultural competence due to superficial coverage and underrepresentation of minority cultures. The study highlights the need for richer, more inclusive cultural narratives, such as case studies and reflective tasks, to encourage deeper understanding and critical thinking. By addressing these gaps, educators and curriculum developers can create materials that better align with the Merdeka Curriculum’s vision of contextual and meaningful learning. Furthermore, this study contributes to English language education by emphasizing the role of cultural representation in fostering students' intercultural competence, which is essential for effective communication in global context.